Abnormalities of effective connectivity and white matter microstructure in the triple network in patients with schizophrenia. (August 2020) - Kang, Yafei; Huang, Kexin; Lin, Yanyan; Xu, Hanxiao; Zhang, Wei; Lv, Yahui; Cai, Suping; Huang, Liyu
Highlights: Abnormal effective connectivity between SN and CEN. Abnormal FA in CEN. Abnormal FA in bilateral anterior corona radiate, which correlated with the severity of positive symptoms. Abstract: Disorganized communication among large-scale brain networks, especially in the salience network, default mode network and central executive network, have been consistently reported in schizophrenia (SZ) patients. However, abnormal patterns of the effective connectivity and abnormalities in the white matter of these networks remains unclear in patients with SZ. Fifty-six SZ patients and fifty-five healthy controls were enrolled in the present study and underwent resting state functional magnetic resonance and diffusion tensor imaging. Twelve main nodes within the triple networks were defined by independent components analysis. Effective connectivity between these main nodes was computed using Granger causality analysis. Voxel-based analysis of the diffusion tensor imaging data was conducted to explore white matter changes. The SZ patients showed abnormal effective connectivity between the anterior cingulate cortex and the dorsolateral prefrontal cortex. The abnormal white matter showed decreased fractional anisotropy localized in the bilateral anterior corona radiate and left superior long fasciculus in patients with SZ. These findings shed light on the importance of the triple network in the pathogenesis of SZ, which may facilitate the understanding of SZ.